TURN OF WORLD TRADE ORGANIZATION IN ACHIEVING SUITABLE LEVELS OF FOOD SECURITY IN LOW INCOME COUNTRIES - Fadwa Ali Hussein (Mesopotamia Journal of Agriculture)
The study depended on a hypothesis that world trade organizations policies have various impacts on achieving food security levels in the developing countries in accordance with the economic structures and the level of their economic growth for the period 1975-2003. To approve this hypothesis a sample of the developing countries was selected including Egypt, Morocco, Tunisia, Jordan, Syria, Turkey, Thailand and Pakistan. Time series data were used in estimating the phenomenon under study for each country as they reflect the effects of World Trade Organization policies in achieving levels of food security. The following results were driven: Agricultural economic revealing variable contributed in increasing the agricultural gap value with (37.5%) of the sample countries and the other part of the effect was distributed between either negative or neutral in other states. Positive effects in direct foreign investment to total local product was (50%) of the agricultural gap for the sample countries and the negative and neutral effects were for other countries. The study recommends the following : Improving the competitive ability of the agricultural products in the local and international markets under the current economic transformations imposed by the World Trade Organization agreements by increasing the level of the agricultural production that is one of the pillars that economic integration should depend on in the developing countries. Separating economic work from policy through agreements to achieve Arabic economic integration partially and totally.